2008
DOI: 10.1253/circj.72.150
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Therapy Applied to Rat Bone Marrow-Derived Mononuclear Cells Enhances Formation of Cells Stained Positive for CD31 and Vascular Endothelial Growth Factor

Abstract: Background This study tested the hypothesis that shock wave (SW) therapy applied to bone marrow-derived mononuclear cells (BMDMNCs) enhances the formation of vascular endothelial growth factor (VEGF) and positively stained CD31 (CD31+) cells, an endothelial phenotype. Methods and ResultsThe BMDMNCs (~1.2×10 6 cells/2 femoral bones) were obtained from adult male Sprague-Dawley rats and SW therapy was applied once to BMDMNCs in group I (140 SW: defined as 140 shots in total, given at 0.09 mJ/mm 2 ), group II (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 31 publications
(119 reference statements)
1
31
0
Order By: Relevance
“…More importantly, our findings suggest that the new vessel formation is the result of angiogenesis and vasculogenesis and the effects of cytokines following BMDMNC transplantation. Interestingly, in vitro studies 32,33 have recently demonstrated that either cytokine or shock wave therapy applied to BMDMNC can enhance angiogenesis, expression of vascular endothelial growth factor, and positive CD31 cellular staining. Other recent investigations [5][6][7]34,35 have also shown that autologous bone marrow cell transplantation elicits angiogenesis, which in turn improves ischemia-induced organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, our findings suggest that the new vessel formation is the result of angiogenesis and vasculogenesis and the effects of cytokines following BMDMNC transplantation. Interestingly, in vitro studies 32,33 have recently demonstrated that either cytokine or shock wave therapy applied to BMDMNC can enhance angiogenesis, expression of vascular endothelial growth factor, and positive CD31 cellular staining. Other recent investigations [5][6][7]34,35 have also shown that autologous bone marrow cell transplantation elicits angiogenesis, which in turn improves ischemia-induced organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it remains to be examined whether our SW therapy promotes recruitment of bone marrow-derived cells by the ischemic myocardium of humans. 14, 15 Fourth, the detailed molecular mechanisms of the beneficial effects of SW in humans remain to be clarified in future studies. [3][4][5][6][7] In conclusion, the present double-blind, placebo-controlled study further confirmed the effectiveness and safety of our extracorporeal cardiac SW therapy for the treatment of severe angina pectoris, although large-scale multi-center study is needed.…”
Section: Double-blind Placebo-controlled Study Of Sw Therapymentioning
confidence: 99%
“…Low-energy SW therapy has been reported to promote migration and differentiation of bone marrow-derived mononuclear cells (32,42), and the effects of the combination therapies of cell transplantation and SW have also been reported (2,5). Understanding of the detailed mechanisms of SW-induced angiogenesis may enable us to develop new therapeutic strategies (e.g., combination of pharmacotherapy and SW therapy).…”
Section: Discussionmentioning
confidence: 99%